Preoperative planning for a multi-arm robot-assisted minimally invasive surgery system. (October 2017) - Du, Zhijiang; Wang, Wei; Wang, Weidong; Dong, Wei
The preoperative preparation of robot-assisted minimally invasive surgery is more critical and complicated than traditional minimally invasive surgeries. The crucial issues in preoperative planning are presented and investigated in this paper, in which a new dexterity index IICV and an intracorporeal collaboration space index IICS are proposed for robot-assisted minimally invasive surgery. The kinematic performance of the robotic manipulator, the visual field conditions, and the cooperation space of the instrument are considered. A set of multi-objective preoperative optimization methods based on non-dominated sorting genetic algorithm 2 (NSGA-II) is designed, which is used to simultaneously optimize the incision placement and the initial pose of the manipulator. The simulation experiment results show that the preoperative planning scheme obtained by the optimization algorithm can provide a relatively superior operating environment for robot-assisted minimally invasive surgeries.